Evaluation of fetal anomalies by two-and three-dimensional ultrasound - (:unkn) unknown (My University, 2007)
Objective. To assess clinical impact and the potential of three-dimensional ultrasound (3D US) for prenatal evaluation of fetal malformations compared to two-dimensional ultrasound (2D US). Clinical impact of 3D US in the cases with anomalies were determined. Methods. Seventy-six patients with 190 anomalies were scanned prospectively with both 2D and 3D US by two fetal medicine specialists who have extensive experience in 3D US. Each anomaly was reviewed again to determine whether the 3D US data were advantageous when compared to 2D US images. Results. The 3D US images provided additional information in 130 (69%) anomalies, were equivalent to 2D US images in 60 (31%) anomalies and were not disadvantageous in any of the cases. The 3D US was particularly helpful in evaluating fetuses with craniofacial anomalies, spinal defects, thoracic abnormalities, body surface and extremities. Conclusion. In comparison with 2D US, 3D US offers more diagnostic information in evaluating fetal malformations, particularly in displaying fetal malformations of the face and cranium, spine, extremities, and body surface. 3D US is an excellent adjunctive tool to 2D US in the evaluation of fetal anomalies.
Keywords: Fetal anomalies; Prenatal diagnosis; Three-dimensional ultrasound